THE EFFECT OF VALUE CHAIN CONCEPT, TECHNOLOGICAL INNOVATION, ACCESS TO FINANCING, AND GOVERNMENT POLICY ON VALUE ADDED AN IMPLICATIONS FOR INCOME QUALITY OF COFFEE COMMODITY FARMERS IN KERINCI REGENCY, JAMBI, INDONESIA - Heppi Syofya (ITB AAS Indonesia Surakarta, 2024)
Abstract This study examines how government policies, technological innovation, financing availability, and the value chain concept interact to affect the income quality and value added of coffee commodity producers in Kerinci Regency, Jambi, Indonesia. Structural Equation Modeling with Partial Least Squares (SEM-PLS) was used in a quantitative analysis with 200 farmers as a sample to evaluate the correlations between the important variables. The findings show a strong positive correlation between the variables under investigation and the value added in coffee production as well as income quality. For policymakers, practitioners, and researchers looking to improve the financial security of the region's coffee producers, these findings offer insightful information. Keywords: Value Chain Concept, Technological Innovation, Financing, Government Policy, Value Added, Income Quality, Coffee, Kerinci Regency, Indonesia